2016
DOI: 10.1021/acsami.6b01117
|View full text |Cite
|
Sign up to set email alerts
|

Copper Mesh Templated by Breath-Figure Polymer Films as Flexible Transparent Electrodes for Organic Photovoltaic Devices

Abstract: PSS (5.2 eV) hole extraction layer. The modified Cu mesh electrodes show remarkable potential as a substitute of ITO/PET in the flexible OPV and OLED devices. The OPV cells constructed on our Cu mesh electrodes present a similar power conversion efficiency of 2.04% as those on ITO/PET electrodes. The flexible OLED prototype devices can achieve a brightness of 10 000 cd at an operation voltage of 8 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 39 publications
3
51
0
Order By: Relevance
“…However, ITO films are not applicable to flexible OLEDs because they are brittle. Therefore, many substitutable electrodes have been investigated to replace ITO films such as carbon nanotubes, graphene, conductive polymers, and metal‐based electrodes . Among the alternatives, metal‐based electrodes are a strong candidate due to their superior electrical and optical transmittance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ITO films are not applicable to flexible OLEDs because they are brittle. Therefore, many substitutable electrodes have been investigated to replace ITO films such as carbon nanotubes, graphene, conductive polymers, and metal‐based electrodes . Among the alternatives, metal‐based electrodes are a strong candidate due to their superior electrical and optical transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…Cu‐based electrodes have been attractive as a substitute for ITO because of their cost‐efficiency. However, Cu‐based electrodes are easily oxidized at low temperature and have lower conductivity and transparency than Ag . On the other hand, the reports of Ag‐based electrodes have been numerous due to its excellent performances such as high electrical conductivity and transparency.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter and degree of ordering of the can be seen to increase for the films made under an air flow humidity of 59% and 74% and further towards a value of RH-F equal to 89% (Figure 4.7), in agreement with previous observations. 10,52,53 It can be concluded that a threshold level of moisture is required for the formation of ordered patterns, within the range of 45% to 50%, in line with previous reports. 54 Numerical analysis has shown that the threshold humidity or the cut-off of condensation is related to the saturation of the vapour as the temperature decreases, 48 which is correlated with the convection and the growth of water droplets.…”
Section: Effect Of Relative Humidity Of the Air Flowsupporting
confidence: 89%
“…Besides the template fabricated through photolithography, the periodic or random arranged microspheres on substrate can also act as the template for the deposition of metal film with micrometer size holes, which allow the penetration of light . Thin film with the formation of cracks inside, in most cases, is normally regarded as poor quality.…”
Section: The Front Metal Electrodementioning
confidence: 99%